The Role of Parents in Overcoming Moral Crisis in the Household - Fitriani, Fitriani; Syafrizal, Syafrizal; Aftika, Aftika; Nurdianna, Nurdianna; Putri, Berlianda Indah; Guspita, Rosi; Alias, Muhamad Firdaus Bin (Sekolah Tinggi Agama Islam YDI Lubuk Sikaping, 2023)
The role of parents in building a good household is very important. In instilling noble morals in children, parents are required to have various strategies so that their children's morals are formed according to what is expected. Parents' strategies for playing a role in dealing with moral crises in children and households cannot be separated from the Quran. This research aims to analyze Luqman's advice to his children based on the content of Surah Luqman verses: 13-19. This research uses a qualitative method with a content analysis approach, all data is taken from various sources originating from the Quran, theories and opinions of Islamic education experts. Then a theme is taken that matches the required data. After the author has collected all the data, the next step is to select the required data according to the problems raised in this article. Based on Luqman's letter, there are nine roles of parents in dealing with a moral crisis in the household, namely providing an example to children, always being ready to be a good listener, spending time together with family, giving clear expectations to children, don't let yourself feel guilty, don't replace love or time with money, don't change caregivers frequently, provide supervision, and provide punishment to educate.